Clove Oil (Syzygium aromaticum) Edible Film Formulation and Antibacterial Activity Test against Streptococcus mutans - Wida Ningsih; Afdhil Arel (Universitas Muhammadiyah Yogyakarta, 2021)
Clove oil contains eugenol as an antibacterial. Meanwhile, products containing clove oil have been widely used as toothpaste and mouthwash. In this study, clove oil was formulated in the form of edible film because it is practical, easy to use, and could be used without water like other oral hygiene preparations. The edible film is a thin layer film made of consumable materials used as a carrier of antibacterial compounds. Clove oil edible film was then formulated with clove oil concentrations of 1%, 1.5%, and 2% and determined for its antimicrobial activity against Streptococcus mutans. Clove oil edible film preparations were evaluated under their physical properties, including friability, drying shrinkage, pH, thickness, and swelling ability. Antibacterial activity testing of clove oil edible film was conducted, employing the blood agar diffusion method against Streptococcus mutans. The physical evaluation of the clove oil edible film showed almost the same physical properties as the comparison (GF). Clove oil edible film test results revealed the greatest inhibition at F1 of 18.6 mm is more or less 0.577, F2 of 22.3 mm is more or less 2.081, and F3 of 25.3 mm is more or less 1.527. According to David and Stout, the inhibition activity of bacteria on F3 was categorized as a very strong group inhibition response. In addition, ANOVA test analysis results uncovered that the concentration of clove oil affected the inhibition of the Streptococcus mutans bacteria with a significance value of 0.000 (p less than 0.05). Also, Duncan's test exhibited that each concentration of clove oil had a significant difference in the inhibition of Streptococcus mutans bacteria.